Postmodern Theology : a Biopic. - Raschke Carl A. (Cascade companions ;)
Postmodern Theology consists in a sharp-edged retrospective and reflection on the forty-year history of the most important movement in contemporary religious thought that is only now passing from the scene. The author, Dr. Carl Raschke, is generally credited with having sparked the movement, even if he did not always happen to be its leading spokesperson. Not only has a comprehensive survey of postmodern theology in all its different phases and complexity not been published prior to the appearance of this book, but it is even more remarkable for someone who both ""launched"" it and had a centr.